Construction process innovation on Brock Commons Tallwood House. Issue 1 (25th January 2021) - Staub-French, Sheryl; Pilon, Angelique; Poirier, Erik; Fallahi, Azadeh; Kasbar, Mohamed; Calderon, Francisco; Teshnizi, Zahra; Froese, Thomas
Abstract : Purpose: The purpose of this paper is to present the construction process innovations that enabled the successful delivery of the hybrid mass timber high-rise building in Canada, the Brock Commons Tallwood House at the University of British Columbia. It is one of a set of papers examining the project, including companion papers that describe innovations in the mass timber design process and the impact of these innovations on construction performance. The focus of this paper is on innovation in the construction phase and its relationship to innovations implemented in previous project phases. Design/methodology/approach: A mixed-method, longitudinal case study approach was used in this research project to investigate and document the Tallwood House project over a three-year period. Both quantitative and qualitative data collection and analysis techniques were used. Members of the research team observed prefabrication and construction, conducted periodic interviews and reviewed project artefacts. Findings: The research identified three innovation "clusters, " including the use of innovative tools, techniques and strategies in the design and construction processes and the role they played in delivering the project. The "clusters" were further characterized according to the type of "connectivity" they afforded, either facilitation, operationalization or materialization. These two perspectives support a compounding view on innovation and help to understand how it can flow throughout a project's life cycle and across its supply chain. Three process-based innovations were initiated during the design phase, integrated design process, building information modeling and virtual design and construction and flowed through to the construction phase. These were seen to enable the creation of connections that were crucial to the overall success of the project. These innovations were operationalized and enacted through the construction phase as design for manufacturing and assembly and prefabrication, staged construction and just-in-time delivery, integration of safety and risk management and a rigorous quality control and quality assurance process. Finally, a full-scale mock-up was produced for practice and constructability assessment, materializing the radical product innovation that was the mass timber structure. These strategies are used together for a synergistic and integrated approach to increase productivity, expedite the construction schedule and develop an innovative building product. Originality/value: This paper details an in-depth investigation into the diffusion dynamics of multiple systemic innovations for the construction process of a unique building project, the tools and techniques used by the construction manager and team, and the challenges, solutions and lessons learned.